2014
DOI: 10.1167/iovs.13-12574
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Neonatal Fc Receptor in the Eye

Abstract: METHODS. We used qPCR to study mRNA expression of the transmembrane chain of FcRn (FCGRT) in retina, optic nerve, RPE/choroid plexus, ciliary body/iris plexus, lens, cornea, and conjunctiva isolated from mouse, rat, pig, and human postmortem eyes and used immunohistochemistry to determine the pattern of FcRn expression in FCGRT-transgenic mouse and human eyes.RESULTS. In all four tested species, Fcgrt mRNA was expressed in the retina, RPE/choroid, and the ciliary body/iris, while immunohistochemistry documente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
34
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(35 citation statements)
references
References 32 publications
1
34
0
Order By: Relevance
“…It has been determined that the FcRn is responsible for the active transport of molecules containing an Fc domain across the blood retinal barrier and it therefore increases the overall bioavailability. This makes the FcRn clinically relevant not only for the intra-ocular pharmacokinetics of therapeutic monoclonal antibodies, but also for the offtarget effect on VEGF in the periphery by actively transporting the anti-VEGF agents from the vitreous into the systemic circulation (Roopenian & Akilesh 2007;Powner et al 2014;Proetzel & Roopenian 2014). Upon reaching the blood stream, the duration of the anti-VEGF effect is contingent on its systemic half-life.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been determined that the FcRn is responsible for the active transport of molecules containing an Fc domain across the blood retinal barrier and it therefore increases the overall bioavailability. This makes the FcRn clinically relevant not only for the intra-ocular pharmacokinetics of therapeutic monoclonal antibodies, but also for the offtarget effect on VEGF in the periphery by actively transporting the anti-VEGF agents from the vitreous into the systemic circulation (Roopenian & Akilesh 2007;Powner et al 2014;Proetzel & Roopenian 2014). Upon reaching the blood stream, the duration of the anti-VEGF effect is contingent on its systemic half-life.…”
Section: Discussionmentioning
confidence: 99%
“…Aflibercept contains a Fc fragment like bevacizumab and therefore interacts with the neonatal Fc receptor (FcRn). The FcRn enables these molecules to readily cross the blood-retina barrier, thus giving access to systemic circulation (Krohne et al 2014;Powner et al 2014). Study results describing systemic angiogenic cytokine alterations induced by intravitreal aflibercept have been published recently, and significant systemic exposure resulting from accumulation of active VEGF blocking substance was detectable after intravitreal aflibercept applications Wang et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…10 Recent studies reported that the elimination of intravitreally administered IgG across the blood-retina barrier into the systemic circulation is mediated by the neonatal Fc receptor (FcRn), which is expressed in the retinal pigment epithelium and endothelial cells of the retinal and choroidal vasculature. [11][12][13] Ocular application of the Fcbased fusion proteins is a relatively new advance, and whether their elimination or transport depends on FcRn and/or the molecular weight remains unclear. Understanding of the role of the Fc region and FcRn in intraocular pharmacokinetics (PK) is important in determining the duration of therapeutic efficacy of drugs as well as in anticipating the systemic exposure of intravitreally injected anti-VEGF agents, which can potentially cause systemic complications.…”
mentioning
confidence: 99%
“…In addition, the presence and affinity of the Fc portion of anti-VEGF agents may affect the exposure ratio in the retina/choroid. [24][25][26] We are currently assessing the role of Fc portion of anti-VEGF agents in intraocular distribution and elimination. We believe that this will improve our understanding of intraocular PK in anti-VEGF agents.…”
Section: Discussionmentioning
confidence: 99%